MOLECULAR DOCKING OF AMITRIPTYLINE TO CERULOPLASMIN, RETINOL-BINDING PROTEIN, AND SERUM ALBUMIN - Merugu, Ramchander; Singh, Kalpana V (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Â Objective: A drug’s efficiency depends on the binding capacity of the drug with the particular plasma protein. The less bound drug can be easily diffused through cell membranes. The present study deals with in silico studies of amitriptyline binding to three plasma proteins human ceruloplasmin (HCP), cellular retinol-binding protein (CRBP), and human serum albumin (HSA) and tries to establish the binding capacity behavior with the frontier molecular orbital approach. Methods: Amitriptyline is selected as legend and docked with three plasma proteins HCP, HCP PDB ID 1KCW, CRBP PDB ID 5LJC, and HSA. Docking calculations were carried out using docking server. frontier molecular orbital calculations are performed through web-based computational chemistry interface WEBMO version 17.0.012e using server Buchhner.chem.hope.edu. on computational engine MOPAC. Results: HCP and HSA predominantly show polar and hydrophobic interactions, whereas CRBP forms hydrogen bond apart from polar and hydrophobic interactions. Favorable values of inhibition constant, Ki, is obtained which is equal to 1.13 Î¼M for CRBP, 6.00 Î¼M for HCP, and 2.00 Î¼M for has. Conclusion: A studies prove that amitriptyline can bind to all three plasma proteins, namely, HCP, CRBP, and HSA. Amitriptyline binds to an HSA and HCP through polar and hydrophobic interactions while weak electrostatic interactions felicitate diffusion of amitriptyline through the plasma membrane. Comparatively, strong hydrogen bond in CRBP may make the bound drug to be released at a slow rate. Strong binding of amitriptyline to CRBP is also evident from the least value of inhibition constant, Ki, which is equal to 1.13 Î¼M for CRBP, 6.00 Î¼M for HCP, and 2.00 Î¼M for has.